IMPLEMENTASI SISTEM AKUNTANSI ACCURATE DALAM PENYUSUNAN LAPORAN KEUANGAN (STUDI KASUS PADA UMKM CAH ANGON BREBES) - Kartika, Dewi; Kholifah Fil Ardhi; Gita Ismi Fauziyah (Universitas Sulawesi Barat, 2025)
This study Implementation of accurate accounting system in the preparation of financial statements (case study on MSMEs Cah Angon Brebes). This study aims to determine the implementation of the accurate accounting system in the preparation of financial statements (case study on MSMEs cah Angon Brebes). Research methodology through data collection techniques consists of observations, interviews, literature studies, and documentation. Meanwhile, data analysis techniques consist of data collection, reduction, data presentation data, and drawing conclusions. The results of this study are expected to provide input to MSMEs about manual recording will produce financial statements that are less reliable and not in accordance with financial reporting standards, in accordance with the outline of how financial statements are made, After the implementation of making financial statements computerized using the financial application Accurate Education Book Version 5, produce financial statements that start well and accurately, are easy to use at any time and can be used as documents that can be attached when applying for capital in banking.